Analisis Literatur Mengenai Peran Manajemen Data dalam Membentuk Scroll Behavior Generasi Z di Tiktok - Nadin Khairunisha; Muhammad Irwan Padli Nasution (International Forum of Researchers and Lecturers, 2026)
The development of short video based social media, particularly TikTok, has led to significant changes in the digital behavior patterns of Generation Z. This study aims to analyze the role of data management within the TikTok system and its influence on user scrolling behavior. The method used was a qualitative approach using the Systematic Literature Review (SLR) technique of various relevant journals and scientific articles. The result show that data management is the primary basis for developing TikTok’s algorithm, which generates personalized content on the For You Page (FYP) feature. This algorithm works by utilizing user interaction data, such as viewing duration, content preferences, and engagement levels, thus presenting content tailored to user interests. Furthermore, this behavior is influenced by psychological factors, such as the need for entertainment and instant gratification, as well as app design factors, such as the infinite scroll feature and ease of navigation. Consequently, despite the benefits of accessing information and entertainment, excessive use has the potential to cause negative effects, such as digital addiction and decreased concentration.